Assessment of free-edge singularities in composite laminates using higher-order plate elements. Issue 9 (1st September 2016) - Wenzel, C.; D'Ottavio, M.; Polit, O.; Vidal, P.
Abstract: The capabilities and limitations of refined two-dimensional (2D) composite plate elements are discussed with respect to the stress concentration problem occurring at traction-free edges. Classical displacement-based and advanced partially mixed finite elements are formulated according to Carrera's Unified Formulation (CUF). Rectangular laminates are analyzed under extension and bending loading, where the attention is focused on the local stress response at the free edges. Present results are compared with reference results available in the literature and a 3D finite element model. A power law representation for a singular stress field is used to fit the obtained stresses in the vicinity of the free edge, and the parameters are used to assess the CUF elements and to compare the free-edge effect occurring in extension and bending.